2004
DOI: 10.1270/jsbbs.54.215
|View full text |Cite
|
Sign up to set email alerts
|

Soybean Genomics: Efforts to Reveal the Complex Genome

Abstract: Soybean (Glycine max (L.) Merrill) is the most important leguminous crop in the world due to its highest content of high-quality protein for food and feed, and its capacity of oil production for food and industrial materials. Physiologically functional constituents in soybean seeds contribute significantly to human health, and because of its characteristic symbiosis with root bacteroids, soybean supplies nitrogen to soil. Although soybean has a relatively large and complex genome, several methods for genome an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 123 publications
0
8
0
Order By: Relevance
“…One of the most important legume crops in the world, soybean is well known for its high content of good quality seed protein for food and feed purposes, and also for its capability for providing oil needed for industry (Harada and Xia 2004). Soybean seeds also contain sufficient amount of phosphorus required for human health and optimal livestock production, in the form of inositol hexaphosphate otherwise known as phytate (Raboy 2007).…”
Section: Introductionmentioning
confidence: 99%
“…One of the most important legume crops in the world, soybean is well known for its high content of good quality seed protein for food and feed purposes, and also for its capability for providing oil needed for industry (Harada and Xia 2004). Soybean seeds also contain sufficient amount of phosphorus required for human health and optimal livestock production, in the form of inositol hexaphosphate otherwise known as phytate (Raboy 2007).…”
Section: Introductionmentioning
confidence: 99%
“…If late maturity confers resistance, it might be difficult to develop elite pest-resistant cultivars. We would also face the same difficulty if the genes for resistance and maturity are tightly linked, even though maturity is not the cause of the resistance.Genetic studies on soybean maturity have revealed the positions of some maturity genes and QTLs (Harada and Xia, 2004), but the materials studied were relatively early-maturing cultivars so the effects of the genes and QTLs on the genetic control of late maturity is still unclear. We conducted genetic analysis of the factors involved in the maturity of the Himeshirazu cultivar with the objectives of detecting the positions and effects of QTLs for pubes-…”
mentioning
confidence: 99%
“…Genetic studies on soybean maturity have revealed the positions of some maturity genes and QTLs (Harada and Xia, 2004), but the materials studied were relatively early-maturing cultivars so the effects of the genes and QTLs on the genetic control of late maturity is still unclear. We conducted genetic analysis of the factors involved in the maturity of the Himeshirazu cultivar with the objectives of detecting the positions and effects of QTLs for pubes-cence density and maturity of pest-resistant soybean and also to clarify the effects of pubescence density and maturity on pest resistance.…”
mentioning
confidence: 99%
“…Genomic fragments encoding GmPDIL‐1 and GmPDIL‐2 were isolated from the transformation‐competent artificial chromosome (TAC; pYLTAC7) library of the soybean variety ‘Misuzudaizu’ by three‐dimensional screening [45,46]. Screening was performed by PCR using the oligonucleotide primers 5′‐CCCAATTTGGAAGCTGATCACAT‐3′ and 5′‐CTTCCTTGGTCCTACCCCCTTCGT‐3′ for GmPDIL‐1 , and 5′‐AGCCCGAGGTGGACGAGAAGG‐3′ and 5′‐TTTGCCACATCAGGATCCACAGTTT‐3′ for GmPDIL‐2 , and sequencing.…”
Section: Methodsmentioning
confidence: 99%